Women in peace and international security in Argentina: The case of women scientists in the navy (1981–2016) - Fuente, María del Rosario de la (2023)
Fil: Fuente, María del Rosario de la. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina